Diaquabis(perchlorato)(1,10-phenanthroline)copper(II) - Kamel Kaabi; Meher El Glaoui; Matthias Zeller; Cherif Ben Nasr (Acta Crystallographica Section E, 2010)
In the title compound, [Cu(ClO4)2(C12H8N2)(H2O)2], the CuII atom is coordinated in a square-planar fashion by the two N atoms of a chelating 1,10-phenanthroline ligand and by two water molecules trans to the N atoms. The coordination sphere of the metal atom is augmented by O atoms of two weakly bonded perchlorate anions, thus yielding a strongly distorted CuN2O4 octahedral environment. The crystal packing is stabilized by O—H...O hydrogen bonds between the water molecules and the perchlorate anions. In addition, the organic molecules are associated by π–π stacking interactions between symmetry-equivalent antiparallel non-nitrogen aromatic rings, with interplanar distances of 3.543 (2) Å.